Defending Tennyson - Colón, Christine A. (Christianity & literature, 2017)
Dorothy L. Sayers’s interactions with Tennyson’s poetry provide a powerful example of her theology of charitable reading. Unlike many of her contemporaries, Sayers refused to oversimplify Tennyson’s works. She defended him from his critics and used some of his ideas to inform Gaudy Night, crafting an insightful critique of The Princess that acknowledges the poem’s problems but also emphasizes its underlying truths. Sayers never completely articulated her theology of charitable reading, but with her approach to Tennyson, she enacts the theology that is implicit in her reflections on the artist in The Mind of the Maker.